MENJAGA PROBITY DALAM PANDEMI: TINJAUAN PROSEDUR AUDIT ATAS PENGADAAN BARANG/JASA TERKAIT PENANGANAN COVID-19 - Candra Hapsari Susilo (Politeknik Keuangan Negara STAN, 2022)
Public procurement is one of the riskiest target of corruption. Probity audit is one of the measures taken by Indonesia’s Government to prevent such fraud. However, the pandemic has posed a great challenge for auditors in order to maintain reasonable assurance. Key aspects of evidence-gathering such as physical examination, are unable to be done. Seeing that, this research aims to understand as well as shed light on the alternative procedure auditors can perform amidst the restriction caused by the pandemic. The object of research is the audit of the procurement of COVID-19 Emergency Hospital in Lamongan, carried out by BPKP Jawa Timur. The results has shown that auditors mainly focuses on desk auditing, with heavy reliance on papers and document and minimal physical examination. In terms of maintaining probity, instead of fully auditing, controls and surveillance are done in two parts, which is advising during the planning stages, and auditing. Such steps are taken due to the fact that the aren’t any regulation regarding audits of public procurement during COVID-19 emergencies yet as of the start of procurement.